AUDIT UNTUK PERUSAHAAN KECIL - Dul Muid (Universitas Islam Nahdlatul Ulama Jepara, 2006)
AbstractThe obligations placed upon the auditor by the companies acts have universal application, and the some requirements for the audit at annual financial statement apply to all companies irrespective of their size However, in practice, there may be many different between the audits of large and small companies In general ihe audit of small companies bear wry little resemblance in scope, conduct and purpose to the audit of their large counterpart, other than la the production oj an audit report which refers to the some legal requirementsArising out of general concern about the legislative burden placed upon unall companies, the need for the publication ofa/ull set of annual Jlnanciul statements has been questioned, linked to this discussion is ihe issue of what is the purpose oj the audit of small companies. where, lit many cases, the managers and shareholders are the same small group of individualSo. for reasons to do with both the usefulness and the practice of auditing, the nature of the audit of small companies requires assessmentKeywords Auditor, Audit, Smallcompanies